2020
DOI: 10.1038/s41598-020-76043-z
|View full text |Cite
|
Sign up to set email alerts
|

Pooling RT-qPCR testing for SARS-CoV-2 in 1000 individuals of healthy and infection-suspected patients

Abstract: Severe acute respiratory coronavirus 2 (SARS-CoV-2) testing reagents are expected to become scarce worldwide. However, little is known regarding whether pooling of samples accurately detects SARS-CoV-2. To validate the feasibility of pooling samples, serial dilution analysis and spike-in experiments were conducted using synthetic DNA and nucleic acids extracted from SARS-CoV-2-positive and -negative patients. Furthermore, we studied 1000 individuals, 667 of whom were “healthy” individuals (195 healthcare worke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Second, a limited testing capacity and weak logistics in procuring personal protective equipment will be demanding. Adopting a pooling strategy [31][32][33] will dramatically dilate Japan's testing capacity and make it possible to repeatedly provide RT-PCR testing. Importing appropriate testing kits for truly recognizing infectiousness based on the previous discussion [34] will be a policy option, although it can be a debatable political choice in terms of health security.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a limited testing capacity and weak logistics in procuring personal protective equipment will be demanding. Adopting a pooling strategy [31][32][33] will dramatically dilate Japan's testing capacity and make it possible to repeatedly provide RT-PCR testing. Importing appropriate testing kits for truly recognizing infectiousness based on the previous discussion [34] will be a policy option, although it can be a debatable political choice in terms of health security.…”
Section: Discussionmentioning
confidence: 99%
“…Total nucleic acid was isolated from the samples using the MagMAX Viral/Pathogen Nucleic Acid Isolation Kit (Thermo Fisher Scientific, Waltham, MA, USA) on the KingFisher Duo Prime System (Thermo Fisher Scientific) as we previously described [15, 16]. Briefly, we added 200 µL of VTM, 5 µL of proteinase K, 265 μL of binding solution, 10 μL of total nucleic acid-binding beads, 0.5 mL of wash buffer, and 0.5–1 mL of 80% ethanol to each well of a deep-well 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Hirotsu et al showed that the primer/probe targeting the N1 site succeeded to detect samples with high and moderate viral load, but not those with low viral load when the samples were examined in pools of 20. The N2 site was proven to be more effective target for analyzing the pooled samples, since it was detected even if in cases with low viral load ( Hirotsu et al, 2020 ). Perchetti et al showed that pooling correctly identified SARS-CoV-2 in 94 % of the samples which were classified as samples with median viral load.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%